Analysis of the Influence of Customer Relationship Management on Customer Loyalty: A Case Study of Momoyo Ice Cream - Fahrudin (Asosiasi Ahli Administrasi Indonesia, 2025)
This study analyzes the effect of Customer Relationship Management (CRM) on customer loyalty at Es Krim Momoyo, a growing F&B brand within an increasingly competitive market. The increasing variety of product choices and shifting consumer preferences make customer loyalty a critical factor for business sustainability, particularly for brands with impulsive buying patterns such as ice cream. In this context, CRM becomes an essential strategy for strengthening customer relationships through service quality, employee interaction, communication consistency, and the development of long-term engagement. Using a quantitative approach and survey method, this study examines how CRM is implemented at Momoyo and how it shapes customer loyalty. The findings reveal that effective CRM encourages positive customer experiences, strengthens emotional connections, and increases the likelihood of repeat purchases and recommendations. This study concludes that CRM plays a vital role in building and maintaining customer loyalty, and it should be prioritized as a strategic effort to enhance competitiveness, especially for emerging F&B brands facing intense market dynamics.